Performance Evaluation of Ten Elephant Foot Yam (Amorphophallus paeoniifolius L.) Genotypes in Southwestern Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
Elephant foot yam is a popular South Asian tuber crop and is also widely distributed in Bangladesh. However, genotypes may differ in growth and yield. A field experiment was conducted during the period from March to September 2024 at Dumuria, Khulna, to evaluate ten elephant foot yam genotypes for their growth and yield attributes using a Randomized Complete Block Design with three replications. The genotypes were Kolkata, BAU-1, Satkhira Bagha, Jashore Local, Chuadanga, Madrasi, Bandarban Ruma, Satkhira Local, Sahebi Lomba, and BAU-2. The growth and yield components varied significantly among the genotypes, except for the number of plants per plot. Results revealed that less time was required for sprouting (23.00 days) in Bandarban Ruma. The highest plant height (158.33 cm) was recorded in Madrasi, while the maximum number of leaves was recorded (49.66) in Jashore Local. The highest leaf length and leaf breadth were recorded in BAU-2 (31.66 cm) and Madrasi (22.66 cm), respectively. The maximum corm length and corm diameter were observed in Sahebi Lomba (22.40 cm) and Madrasi (24.33 cm), respectively. The highest corm yield (40.13 t ha-1) was recorded in Madrasi. Overall, Madrasi may be selected for commercial cultivation in the Khulna region.J Bangladesh Agril Univ 23(3): 359–365, 2025